Identification of resident and inflammatory bone marrow derived cells in the sclera by bone marrow and haematopoietic stem cell transplantation. Issue 4 (11th October 2006) - Hisatomi, Toshio; Sonoda, Koh-hei; Ishikawa, Fumihiko; Qiao, Hong; Nakazawa, Takahiro; Fukata, Mitsuhiro; Nakamura, Toru; Noda, Kousuke; Miyahara, Shinsuke; Harada, Mine; Kinoshita, Shigeru; Hafezi-Moghadam, Ali; et al.
Abstract : Aims: To characterise bone marrow derived cells in the sclera under normal and inflammatory conditions, we examined their differentiation after transplantation from two different sources, bone marrow and haematopoietic stem cells (HSC). Methods: Bone marrow and HSC from green fluorescent protein (GFP) transgenic mice were transplanted into irradiated wild-type mice. At 1 month after transplantation, mice were sacrificed and their sclera examined by histology, immunohistochemistry (CD11b, CD11c, CD45), and transmission and scanning electron microscopy. To investigate bone marrow derived cell recruitment under inflammatory conditions, experimental autoimmune uveitis (EAU) was induced in transplanted mice. Results: GFP positive cells were distributed in the entire sclera and comprised 22.4 (2.8)% (bone marrow) and 28.4 (10.9)% (HSC) of the total cells in the limbal zone and 18.1 (6.7)% (bone marrow) and 26.3 (3.4)% (HSC) in the peripapillary zone. Immunohistochemistry showed that GFP (+) CD11c (+), GFP (+) CD11b (+) cells migrated in the sclera after bone marrow and HSC transplantation. Transmission and scanning electron microscopy revealed antigen presenting cells among the scleral fibroblasts. In EAU mice, vast infiltration of GFP (+) cells developed into the sclera. Conclusion: We have provided direct and novel evidence for the migration of bone marrow and HSC cells into the sclera differentiating into macrophages and dendritic cells. Vast infiltration of bone marrow and HSC cells was found to be part of the inflammatory process in EAU.